Economic Contribution of Copyright-Based Industries in Finland 2013 – 2015 - Mikko Grönlund; Tuomas Ranti; Veijo Pönni; Petteri Sinervo (Ministry of Education and Culture, Finland, 2022)
The purpose of the present study was to measure the economic contribution of copyright-based industries to the Finnish economy in 2013, 2014 and 2015 using the World Intellectual Property Organization’s (WIPO) revised methodology in this measurement and to compare the Finnish findings to the results of similar studies completed in other countries.
The key findings of the study include the following:
•
The combined value added of copyright-based industries represented 5.38 percent of the Finnish GDP in 2015 and amounted to €11.27 billion and the combined number of employees in the copyright-based industries amounted to 136 617 and represented 5.61 percent of the total employment in Finland in 2015.
•
From the year 2000 to the year 2015 the economic contribution of core copyright industries has shown a moderate growth. The combined value added of core copyright industries represented 4.14 percent of the Finnish GDP in 2015 (3.28 percent in 2000) amounting to €8.67 billion.
•
Compared to the Finnish GDP growth of 3.04 percent between 2013 and 2015, the value added of core copyright industries in absolute terms grew by 12.73 percent.
•
In 2015, the two largest core copyright industries, software and databases and press and literature, accounted for approximately 85 percent of the cumulative value added of the core copyright industries in Finland.
•
From 2013 to 2015, in the core copyright industries the most prominent growth, in terms of value added, took place in the software industry, whereas the relative contribution of the press and literature and radio and television industry decreased.
•
The revised WIPO Guide on Surveying the Economic Contribution of the Copyright-Based Industries has enabled a very useful increase in the comparability of studies made in different countries. Finland ranks high when it comes to the contribution of the core copyright industries but lower in terms of overall copyright contribution.